Solve for 'x'&'y'

Asked by  | 30th Jan, 2009, 05:59: PM

Expert Answer:

(a+2b)x+(2a-b)y=2 eqn(1)

(a-2b)x+(2a+b)y=3 eqn(2)

by adding both eqn

2ax+4ay=5 eqn(3)

by substracting eqn (2) from eqn(1)

4bx+2by=-1 eqn(4)

on simplifying eqn(3) and (4)

x+2y= 5/2a eqn(3)

2x+y= -1/2b eqn(4)

multiplying eqn (4) to 2 and substracting from eqn (3)

-3x = (5/2a) +(1/b)

x = -(5b+2a)/6ab

eqn(3) Χ2 -eqn(4)

3y = (5/a) +(1/2b)

y = (10b+a)/6ab

Answered by  | 30th Jan, 2009, 07:59: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.